Analysis of Students' Critical Thinking in Geometric Wave Topics: A Study on the Limitations of Student Worksheets in Physics Learning - Noviantoro*, Dwi Ade; Wasis, Wasis; Dwikoranto, Dwikoranto; Prahani, Binar Kurnia; Satriawan, Muhammad; Saphira, Hanandita Veda (Jurnal IPA & Pembelajaran IPA, 2025)
The development of 21st-century learning demands all aspects of development with the integration of technology and innovation so it becomes a challenge in the world of education. In addition to innovative technology, the challenge in education is to improve students' critical thinking skills (CTS). The purpose of this study is to analyze students' CTS through physics learning based on geometric wave phenomena. The method used in this study is quantitative descriptive. Data collection techniques are obtained from observation results, critical thinking test instruments, and student response questionnaires. Data analysis techniques using EFA (exploratory factor analysis) include the eigenvalue factor and alpha Cronbach (MPF and BAPF). Based on the results of the CTS questionnaire, 75 students have low CTS with EFA results on Eigenvalue obtaining values from two factors of 0.507 and 0.907, then the Cronbach alpha value on two factors (MPF and BAPF) is 0.825 and 0.443. The results show that the level of CTS is included in the low category with a score of 13.75%. One of the factors that results in low skill scores is the lack of facilities in the form of interactive LKPD teaching materials